Pengaruh Global Investment Climate Change dan Inflasi terhadap Nilai IHSG Indonesia 2016-2019 - Rosdita Indah Yuniawati; Puji Lestari (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
The purpose of this study was to analyze the influence of the Dow Jones Index and Inflation as proxied by the Consumer Price Index on the composite stock price index on the Indonesian stock exchange. The Composite Stock Price Index (CSPI) serves as an indicator of market trends. This study uses secondary data using the saturated sample method using month-end data from each variable for four consecutive years from 2016-2019. The results revealed that the Dow Jones Index had a significant positive effect on the CSPI and the Consumer Price Index had no effect on the CSPI against the CSPI.